Perancangan Sistem Informasi Persediaan Obat Menggunakan Metode Fifo Berbasis Web Pada Apotek Risma - Muhamad Akbar Putra Prasetyo; Ratna Salkiawati; Achmad Noeman; Nurfiyah (Journal of Informatic and Information Security, 2023)
As for the background that makes this writing, namely, drug data collection at the Risma Pharmacy which still uses the process of recording in books. Problems that often arise with recording in books cause the data to be less accurate, and it is difficult to search for data. Often the pharmacy has difficulty in checking the data of goods in the pharmacy. Recording using multiple ledgers results in inefficient. The method used is the FIFO (First In First Out) method, which is a non-preemptive, non-priority scheduling algorithm. Each process is given an execution schedule based on the order in which it arrives. The development of this system uses the PHP programming language. The system development method uses the RAD (Rapid Application Development) method. This RAD model is very synchronous to realize the form of software with emergency needs and with a short time in the process. The result of this research is a web-based drug supply information system. With this drug supply information system, it can help pharmacies in overcoming drug data collection which was previously processed manually to be more effective because there is no need to record sales data using paper/books.